Comparison of pregnancy outcome in intrauterine insemination-candidate women with and without endometrial scratch injury: An RCT - Mahnaz Yavangi; Nesa Varmaghani; Azar Pirdehghan; Maryam Varmaghani; Mohammad Faryadras (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Endometrial scratch injury is considered controversial in increasing the success rate of assisted reproductive technology. Objective: To compare the pregnancy outcomes in women undergoing intrauterine insemination with and without an endometrial scratch. Materials and Methods: In this randomized clinical trial, 150 women referred to the Fatemieh Hospital, Hamadan, Iran who were candidates for IUI between December 2017 and December 2018 were randomly assigned into two groups (n = 75/each) with or without an endometrial scratch (as case and control groups, respectively). Women in both groups were in proper and identical protocol for IUI. Chemical and clinical pregnancies, abortion, and live birth rate, also pregnancy complications were compared between the groups. Results: Chemical and clinical pregnancy rates were higher in the case than the control group (p = 0.25, p = 0.54, respectively). In the case group, the abortion and multiple gestation rates were 14.3% and 4.3%, respectively, while it was 5% in the control group (p = 0.60, p = 0.54 respectively). The endometrium thickness on day 21 was higher in the case group than the control (p = 0.01). Conclusion: Endometrial scratching in intrauterine insemination women is not associated with an increase in both clinical and clinical pregnancy rates, however, studies with a larger sample size are recommended to evaluate this intervention.